2022
DOI: 10.1021/acsomega.2c02140
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Preparation of Biomass-Derived Porous Carbon and Its Electrochemical Properties

Abstract: High-porosity activated carbon (AC) was prepared from low-cost coconut shells (CS) using KOH as an activating agent with different KOH/char mass ratios. To cut down the amount of KOH used for AC preparation, freezing pretreatment for a certain number of times was carried out on CS before carbonization, which resulted in the maximum increase in the specific surface area ( S BET ) and total pore volume of 92.8 and 44.4%, respectively, in the resultant biochar. For the sake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 55 publications
0
10
1
Order By: Relevance
“…Hou et al [ 97 ] carbonized freeze-dried lotus as a carbon precursor to prepare multi-porous biochar with outstanding microporosity (76.0%). In addition, Wang et al [ 98 ] further explored the influence of the number of freezing times on the freezing treatment effect ( Figure 9 ). It is found that the freezing pretreatment for three times possessed larger specific surface area, microporosity and pore volume, namely that the increase in the number of freeze–thaw cycles was beneficial to form more pores.…”
Section: Pore Size Regulation Methodsmentioning
confidence: 99%
“…Hou et al [ 97 ] carbonized freeze-dried lotus as a carbon precursor to prepare multi-porous biochar with outstanding microporosity (76.0%). In addition, Wang et al [ 98 ] further explored the influence of the number of freezing times on the freezing treatment effect ( Figure 9 ). It is found that the freezing pretreatment for three times possessed larger specific surface area, microporosity and pore volume, namely that the increase in the number of freeze–thaw cycles was beneficial to form more pores.…”
Section: Pore Size Regulation Methodsmentioning
confidence: 99%
“…The specific surface area and pore size distribution are the most important factors affecting the capacitive properties of carbon materials. [21][22][23] Therefore, the morphology and porous structure of LHPCs are studied and shown in Fig. 2.…”
Section: Effect Of Carbonization Temperature On Carbon Yield and Morp...mentioning
confidence: 99%
“…21,22 Biochar has numerous applications in the modern world including food packaging, feed supplementation, 23 filtration of drinking water, 24 hygiene of humans and kitchen waste, cosmetics, 25 and composting agents. It is additionally utilized as an adsorbent in functional clothes and soil enrichment, 26 and as carbon electrodes in supercapacitors for the storage of energy 27 and wastewater treatment. 28 Biochar is a carbon-rich material acquired via the thermochemical transformation of biomass under a controlled atmosphere.…”
Section: Introductionmentioning
confidence: 99%